MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS IV SD NEGERI NO. 14 SIMBOLON PURBA - Pindo Hutauruk; Rinci Simbolon (JURNAL CURERE, 2018)
This research aims the use of teaching problem based learning model can increase result of exam from mathematic student in fourth SD Negeri No 14 Simbolon Purba on basic competencies to solve case about the measure of time, length, and weight. This research is a classroom action research. This subject ot this study are the fourth graders of SD No. 14 Simbolon Purba Samosir which amounted to 20 studensts. Teacher activity observation percentage increase 72.36% from the first stage become 85.52% at the second stage. Student percentage observation increase from 70% become 85% at second stage. The result of research from percentage final classical learning increase from 65% at first stage become 95%at second stage. So it can be concluded using learning problem bases learning model can increase learning outcomes for mathematics in fourth elementary school in SD NEGERI No. 14 SIMBOLON PURBA.